Dimensionamento e contrução de um wetland construído tipo francês para tratamento do efluente de um restaurante universitário - Silva, Rafael Garcia da (2018)
In the present work was carried out the design and construction of a French wetland with partially saturated second stage, developed for the treatment of effluent from a university restaurant. The research is being conducted, in the south of Brazil, more precisely in the city of Londrina (latitude -23.304218, longitude -51.172223), and a site adjacent to the Campus Restaurant. The system has been the subject of research by other students of the Environmental Engineering course and was scaled according to criteria of Molle et. (2005) for French type wetlands, having a first stage bed with a surface area of 1.13m² (Width = 0.90m; Length = 1.25m). The filter mass was composed of 0,10m of gravel 1 (Φ = 9,5-19mm) at the bottom; 0.25m of gravel ½ (Φ = 5-12.7mm) in the intermediate layer and 0.20m of gravel 0 (Φ = 4, 5-9.5mm) in the upper layer. The second stage bed had a surface area of 1 m² and 0.70 m depth of filtering mass, constituted from the bottom to the surface by 0.1 m of gravel 2 (Φ = 19-32 mm), 0.2 m of gravel 1 (Φ = 9.5- 19mm), 0.2m of gravel 0 (Φ = 4.5-9.5mm) and 0.2m of sand (d60 = 0.36mm, d10 = 0.18mm and coefficient of uniformity 2). On the surface of this wetland were planted seedlings of Heliconia Rostrata, (6 seedlings / m²) considering its rusticity, root characteristics and landscape ornamentation provided by its flowers.